The Distribution of Online Reputation: Audience and Influence of Musicians on MySpace - Beuscart, Jean-Samuel; Couronné, Thomas (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
The user-generated content platforms like MySpace, YouTube or Flickr produce emergent sociability patterns and behaviors, which are well observed in various studies. Few of them deal with the nature of the reputation in these large social networks. In this work, we extract a sample of MySpace Music by parsing the artists’ pages and following the "best friend" links. The study of the network shows that the online fame is composed by two independent features: the audience, dominated by the major companies’ artists, and the influence, more associated with independent labels. We observe that most of the audience is focused on a few stars: the tail of MySpace Music is long, but flat. The network structure shows that artists tend to link to artists of similar reputation.